Water Access and Management - UNCTAD (World Bank, Washington, DC, 2018)
This note provides guidance on how to ensure that the impact of agricultural investments on water resources is effectively measured, monitored, and regulated. Water is essential to agricultural production and processing, and has been a driving factor in private and public decisions on where to locate investments. Despite global concerns about water scarcity and pollution, the water use of agricultural investments is in many cases not rigorously measured, monitored, or regulated. Where regulations exist, enforcement is often weak. Some investors improve local water access with community development programs, but such schemes require consultation and careful management.